2014
DOI: 10.5539/ies.v7n3p126
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Decision Making in Academic Dishonesty with Application of Modified Theory of Planned Behavior: A Review

Abstract: This conceptual paper studies the application of the Theory of Planned Behavior (TBP) in academic dishonesty with the mediating variable of ethical ideologies. The study reviews literature on the Theory of Planned Behavior and past studies pertaining to academic dishonesty. The paper analyses the relationship of the variables of TPB on academic dishonesty with ethical ideologies. A conceptual research framework is presented; it provides insight into predicting and understanding how academic dishonesty can occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 62 publications
0
16
0
7
Order By: Relevance
“…Lin and Ding’s 46 research shows that students’ ethical ideologies can differ based on differences in scores on idealism and relativism. 47 Steenhaut and van Kenhove 45 found that highly relativistic individuals are more likely to have a poor judgement of ethical situations compared to individuals scoring low on relativism. A study by Cohen et al 48 suggested that the individuals scoring low on relativism can be more inclined to unethical behaviours compared to individuals scoring high on idealism.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin and Ding’s 46 research shows that students’ ethical ideologies can differ based on differences in scores on idealism and relativism. 47 Steenhaut and van Kenhove 45 found that highly relativistic individuals are more likely to have a poor judgement of ethical situations compared to individuals scoring low on relativism. A study by Cohen et al 48 suggested that the individuals scoring low on relativism can be more inclined to unethical behaviours compared to individuals scoring high on idealism.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Several studies have demonstrated that strong relationships exist between an individual's ethical ideology and (un)ethical behaviours, and the intent of an individual to behave ethically. 38,42,47 Ethical ideology has both a direct and indirect relationship between personal values and ethical beliefs, 49 and significantly influences individual ethical judgement and decision making, and ethical behaviour intentions. 38 McFerran et al 50 demonstrated that ethical ideology mediates the relationship between personality and moral identity.…”
Section: Professional Values In Nursingmentioning
confidence: 99%
“…The theory states that an individual's behavior in a society is influenced by certain factors, deriving from certain reasons and appears in a planned way (Benk, Çakmak, & Budak, 2011). This theory often serves as a determinant of the behavior of technology users (Lu, Zhou, & Wang, 2009;Yousafzai, Foxall, & Pallister, 2010), ethical decision making (Buchan, 2005;Meng et al, 2014), and whistle-blowing (Park & Blenkinsopp, 2009;Zhang, Chiu, & Wei, 2009;Rustiarini & Sunarsih, 2017). Someone does something when he or she considers it as a positive behavior (attitude towards behavior), there is encouragement from the people who are considered important (subjective norms), and there is a belief to do so (perceived behavioral control) (Ajzen, 2001).…”
Section: |mentioning
confidence: 99%
“…Penelitian ini menggunakan Theory of Planned Behavior (TPB) karena banyak peneliti yang menunjukkan bahwa TPB telah menjadi alat yang paling cocok untuk menyelidiki niat terhadap ketidakjujuran akademik (Meng et al, 2014). TPB merupakan perluasan dari Theory of Reasoned Action (TRA).…”
Section: Kerangka Teoretis Dan Pengembangan Hipotesisunclassified